IoT based Smart Home Energy Tracker and Saver - J, Raji Chellam; Raviteja, Bandaru; Reddy, Perla Praveen Kumar; Naidu, Ranganayuni Kishore (IRO Journal on Sustainable Wireless Systems, 2024)
The knowledge about the amount of energy used every month or day at home is the initial step to reduce the energy usage. So, the proposed research focusses on developing a smart energy management system using the IoT to track the daily electricity usage and enhance the energy efficiency at home. The system employs network of sensors placed throughout the home to monitor energy usage in real-time. The information gathered is transmitted to the Blynk Cloud and visualized through the Blynk app. The chart displayed in the Blynk app enables the user to identify the excessive energy usage and reduce both consumption and the electricity bills. By integrating IoT technology and user-friendly control interfaces, this research aims to provide homeowners with actionable insights to minimize energy waste, reduce utility bills, and contribute to environmental conservation.